2022
DOI: 10.33152/jmphss-6.3.11
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Personality Traits on the Life Satisfaction of the Medical Teachers

Abstract: The present study was conducted to examine the effect of personality traits on the life satisfaction of medical teachers. The cross-sectional research design was used to collect data. Data were collected by purposive sampling technique from the medical teachers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The results of zero-order correlations fully confirm the hypothesis H1. Similar to findings from other studies (e.g., [ 14 , 15 , 16 , 17 ] Polish nurses’ LS was related to all FFM traits, negatively to neuroticism and positively to the others, but its correlation with openness to experience was higher than usual (e.g., [ 14 ]) like among medical teachers in Pakistan [ 26 ]. This result will be discussed further.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of zero-order correlations fully confirm the hypothesis H1. Similar to findings from other studies (e.g., [ 14 , 15 , 16 , 17 ] Polish nurses’ LS was related to all FFM traits, negatively to neuroticism and positively to the others, but its correlation with openness to experience was higher than usual (e.g., [ 14 ]) like among medical teachers in Pakistan [ 26 ]. This result will be discussed further.…”
Section: Discussionsupporting
confidence: 87%
“…However, the data contained in these meta-analyses indicate that correlations between FFM traits and SWB constructs may vary by groups. In line with this observation, data collected in different age groups in Poland showed that Openness is more closely related to SWB among adults than adolescents [ 5 ], and among medical teachers in Pakistan the positive correlations of LS with agreeableness (0.64) and openness (0.39) were higher than usual [ 26 ]. Considering that LS of nurses is important for their work performance [ 12 , 13 ] and the satisfaction of patients under their care [ 27 ], there is a need to examine relationships between personality traits and life satisfaction among the professional group of nurses and check whether they are similar to those in the general population.…”
Section: Introductionmentioning
confidence: 80%
“…The results (β = 0.087; T-value = 5.896; p < 0.001) indicate a low intensity but strong positive relation. Previous research did not demonstrate any correlation between individuals' satisfaction and extraversion, but only between extraversion and life satisfaction [57,58], customer well-being [56,60] and life-quality [59]. Extraverts tend to be more satisfied than introverts, associated with a positive impact on customer satisfaction with the fitness center [61].…”
Section: Resultsmentioning
confidence: 90%
“…The importance of extraversion in ensuring the well-being of a customer has also been analyzed [56]. There is a positive relationship between extraversion and life satisfaction [57,58]. Extraversion positively influences life quality, generating satisfaction [59].…”
Section: The Millennials' Behavioral Intention To Practice Fitness 22...mentioning
confidence: 99%